2018
DOI: 10.1007/s00213-018-4870-3
|View full text |Cite
|
Sign up to set email alerts
|

Mining the nucleus accumbens proteome for novel targets of alcohol self-administration in male C57BL/6J mice

Abstract: Protein expression profiling identified an array of proteins and networks in the NAcb, including GSTP1, that are novel molecular targets of chronic alcohol drinking. Pharmacological inhibition of GSTP1 significantly reduced the positive reinforcing effects of alcohol, which regulate repetitive use and abuse liability. The observation that this protein was both upregulated after chronic drinking and that its inhibition could modulate the reinforcing properties of alcohol suggests that it is a key target for alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Mice were singly housed for 2 weeks prior to initiation of home-cage alcohol drinking studies. Voluntary alcohol drinking studies were conducted as previously reported in Hodge et al (1999); Ueno et al (2001); Besheer, Lepoutre, Mole, and Hodge (2006); Stevenson et al (2009); Holstein, Spanos, and Hodge (2011); Agoglia, Holstein, et al (2015); Agoglia, Holstein, Eastman, and Hodge (2016); Salling et al (2016); and Faccidomo et al (2018). Briefly, mice were given continuous 24h access to two 50mL bottles containing sweetened alcohol (25%, w/v + saccharin 0.1%, w/v) or water for 4 months (120 days).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were singly housed for 2 weeks prior to initiation of home-cage alcohol drinking studies. Voluntary alcohol drinking studies were conducted as previously reported in Hodge et al (1999); Ueno et al (2001); Besheer, Lepoutre, Mole, and Hodge (2006); Stevenson et al (2009); Holstein, Spanos, and Hodge (2011); Agoglia, Holstein, et al (2015); Agoglia, Holstein, Eastman, and Hodge (2016); Salling et al (2016); and Faccidomo et al (2018). Briefly, mice were given continuous 24h access to two 50mL bottles containing sweetened alcohol (25%, w/v + saccharin 0.1%, w/v) or water for 4 months (120 days).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were singly housed for 2 weeks prior to initiation of home-cage alcohol drinking studies. Voluntary alcohol drinking studies were conducted as previously reported in Agoglia et al, 2015a;Besheer et al, 2006;Faccidomo et al, 2018;Hodge et al, 1999;Holstein et al, 2011;Salling et al, 2016;Stevenson et al, 2009a;Ueno et al, 2001).…”
Section: -Bottle Home-cage Alcohol or Saccharin Intakementioning
confidence: 99%
“…It has been long known that neural mechanisms of reward and reinforcement underlie the repetitive nature of alcohol-seeking behavior (Hodge et al, 1992(Hodge et al, , 1995(Hodge et al, , 1997Samson & Hodge, 1993;Samson et al, 1992) and promote the development and maintenance of AUD (Koob & Volkow, 2010;Wise & Koob, 2013). Thus, a goal for preclinical AUD medication development is to identify neural targets that drive reinforcement processes and validate compounds that inhibit, or modulate, this action (Anton et al, 1995;Faccidomo et al, 2018;Gorini et al, 2011;Heilig & Egli, 2006).…”
Section: Introductionmentioning
confidence: 99%